Melancholic Identities, Toska and Reflective Nostalgia Case Studies from Russian and Russian-Jewish Culture - Laura Salmon (Biblioteca di Studi Slavistici, 2015)
This book examines the feeling that we often refer to as 'nostalgia' from the perspective of writers and artists located on the (imperial, Soviet, and Post-Soviet) periphery of Russian culture who regard the center of the culture from which they have been excluded with varying degrees of longing and ambivalence. The literary and artistic texts analyzed here have been shaped by these author's ruminations on social and psychological marginalization, a process that S. Boym has called 'reflective nostalgia' and that the authors of this volume also refer to as 'toska'.